Remifentanil and perioperative glycaemic response in cardiac surgery: an open-label randomised trial. (June 2020) - Subramaniam, Kathirvel; Sciortino, Christopher; Ruppert, Kristin; Monroe, Amy; Esper, Stephen; Boisen, Michael; Marquez, Jose; Hayanga, Heather; Badhwar, Vinay
Abstract: Background: This study investigated whether remifentanil infusion decreased intraoperative hyperglycaemia and insulin resistance compared with intermittent fentanyl administration in patients undergoing elective cardiac surgery. Methods: This was a randomised, prospective, open-label trial. Patients undergoing elective cardiac surgery ( n =116) were randomised to receive either continuous intravenous remifentanil infusion or intermittent fentanyl boluses. Hourly blood glucose values were obtained for 24 h starting from induction of anaesthesia. The difference in percentage of patients with ≥2 intraoperative blood glucose concentrations >10 mM (180 mg dl −1 ) between the groups was the primary outcome measure. Secondary outcome measures included insulin requirements, select stress hormone and inflammatory cytokine concentrations, and safety events and adverse outcomes. Results: The trial included 106 subjects in the final intention-to-treat analysis. There were fewer patients with ≥2 intraoperative blood glucose values >10 mM (180 mg dl −1 ) in the remifentanil group (17 [31.5%]) compared with the fentanyl group (33 [63.5%]) (relative risk: 0.50; 95% confidence interval [CI]: 0.32–0.77; P =0.001). The administered intraoperative insulin was a median of 8.1 units (range: 0–46.7) in the fentanyl group and 2.9 units (range: 0–35.1) in the remifentanil group (median difference=5 units; 95% CI: 1–7; P =0.004). Cortisol and adrenocorticotropic hormone were increased less in the remifentanil group ( P <0.001), but there was no relative decrease in this group in select inflammatory cytokines. Postoperative measures of glycaemic control and adverse clinical outcomes were not significantly different between groups. Conclusions: Compared with patients treated with intermittent fentanyl, patients receiving continuous remifentanil infusion had fewer episodes of hyperglycaemia and less need for insulin administration during the intraoperative period of cardiac surgery. Clinical trial registration: NCT02349152 .